Influence of meditation on estate planning decisions: evidence from Indian survey data - Amarjit Gill; Harvinder S. Mand; John D. Obradovich; Neil Mathur (Financial Innovation, 2017)
Background: Intestate death can lead to the distribution of assets against the personal wishes of the deceased and is a problem in India, as 80% of Indians die without making a last will. Following the concepts of decision theory (i.e., the theory of choice), stewardship theory, agency theory, and signaling theory, the purpose of this study is to examine the influence of meditation on estate planning decisions. This study also seeks to extend previous findings on the influence of religious beliefs on the estate planning decisions of Canadians to that of Indians. Methods: Employed and self-employed individuals from India were surveyed regarding their perceptions of meditation and estate planning decisions. Results: The survey indicates that mediation positively influences the estate planning decisions while individuals who practice meditation have greater preferences for estate planning compared with those who do not. The findings suggest that individual assets, family size, and education positively influence the estate planning decisions of Indians. Conclusion: Reported meditation, individual assets, family size, location, education, and gender are positively correlated with the estate planning decisions of Indians.
Keywords: 650; Meditation; Estate planning; Assets; Income; India